The hammon and the beans and other stories - Paredes, Américo, 1915-1999 (Arte Público Press, 2017)
The ongoing struggle of Mexican-Americans between their Mexican past and their American future. The cultural confrontation is taken all the way to the Far East with stories on Mexican-American soldiers fighting the Korean War and living in Japan. By the author of With His Pistol in His Hand: A Border Ballad and Its Hero.